Fam96a is essential for the host control of Toxoplasma gondii infection by fine-tuning macrophage polarization via an iron-dependent mechanism. - Zhuanzhuan Liu; Hanying Wang; Zhiwei Zhang; Yulu Ma; Qiyue Jing; Shenghai Zhang; Jinzhi Han; Junru Chen; Yaoyao Xiang; Yanbo Kou; Yanxia Wei; Lu Wang; et al. (Public Library of Science (PLoS), 2024)
Background Toxoplasmosis affects a quarter of the world's population. Toxoplasma gondii (T.gondii) is an intracellular parasitic protozoa. Macrophages are necessary for proliferation and spread of T.gondii by regulating immunity and metabolism. Family with sequence similarity 96A (Fam96a; formally named Ciao2a) is an evolutionarily conserved protein that is highly expressed in macrophages, but whether it play a role in control of T. gondii infection is unknown. Methodology/principal findings In this study, we utilized myeloid cell-specific knockout mice to test its role in anti-T. gondii immunity. The results showed that myeloid cell-specific deletion of Fam96a led to exacerbate both acute and chronic toxoplasmosis after exposure to T. gondii. This was related to a defectively reprogrammed polarization in Fam96a-deficient macrophages inhibited the induction of immune effector molecules, including iNOS, by suppressing interferon/STAT1 signaling. Fam96a regulated macrophage polarization process was in part dependent on its ability to fine-tuning intracellular iron (Fe) homeostasis in response to inflammatory stimuli. In addition, Fam96a regulated the mitochondrial oxidative phosphorylation or related events that involved in control of T. gondii. Conclusions/significance All these findings suggest that Fam96a ablation in macrophages disrupts iron homeostasis and inhibits immune effector molecules, which may aggravate both acute and chronic toxoplasmosis. It highlights that Fam96a may autonomously act as a critical gatekeeper of T. gondii control in macrophages.